What Influences User Preferences in Digital Payment Systems? (A Comparative Analysis of E-Wallet in Indonesia) - Ina Kartika Wati; A Mukti Soma; Heri Ispriyahadi (Research Synergy Foundation, 2024)
This research explores the growing internet usage and rapid advancements in information and communication technology. Indonesia has witnessed increased adoption of digital financial technology, particularly in the form of fintech and digital payment systems. It is crucial to differentiate the characteristics and advantages among Indonesia’s top three e-wallets: GoPay, OVO, and DANA. This study employs a comparative approach to analyze the relationship between user preferences and factors within GoPay, OVO, and DANA e-Wallets in the context of digital payment systems. Using a quantitative research approach and statistical verification. Data analysis employs SEM with the PLS method, involving 150 respondents whose results are compared across the platforms. The study finds that electronic service quality significantly impacts consumer loyalty and satisfaction across all three platforms. In GoPay and OVO, it notably influences satisfaction, but less so in DANA. Customer satisfaction mediate loyalty in GoPay and OVO but not in DANA. Responsiveness is a key component of e-wallet service excellence. Loyalty is influenced by referrals (GoPay and OVO), regular use (DANA), and pricing (DANA), whereas customer satisfaction (GoPay), pricing (DANA), and convenience (OVO) determine contentment. Limiting the study to three variables and three e-wallets may restrict the comprehensiveness of factors affecting consumer satisfaction and loyalty, potentially limiting the generalizability of findings to other digital payment platforms or market contexts. The novelty lies in the direct comparison of investigative outcomes among these three subjects within the context of digital payment systems, selecting high-value study indicators and advancing the prior research.